2023
DOI: 10.1007/s10826-023-02559-3
|View full text |Cite
|
Sign up to set email alerts
|

Which Space for Fathers’ Mentalizing? A Systematic Review on Paternal Reflective Functioning, Mind-Mindedness and Insightfulness

Abstract: Over the past twenty years research interest has been focused on deepening the role of parental mentalizing. Nevertheless, few studies have specifically addressed the role played by fathers’ mentalizing. This systematic review aims to bridge this gap by offering an exploration of paternal mentalizing within attachment theory considering three different operationalizations: Reflective Functioning, Parental Insightfulness and Mind-Mindedness. Starting from this, the main goals of this systematic review are: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In the meantime, this heightened insecurity contributes to adolescents being more susceptible to developing depression [19]. In addition to the vital impact of both positive and negative paternal coparenting on children's mental health, previous research has also underscored the role of fathers' mentalizing, such as Reflective Functioning, Parental Insightfulness, and Mind-Mindedness, alongside father-child attachment processes and fathers' emotional regulation, in enhancing children's socio-emotional competencies and social adaptation [16,28,[113][114][115]. Thus, future research could integrate these factors comprehensively to thoroughly explore the unique role of fathers in children's development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, this heightened insecurity contributes to adolescents being more susceptible to developing depression [19]. In addition to the vital impact of both positive and negative paternal coparenting on children's mental health, previous research has also underscored the role of fathers' mentalizing, such as Reflective Functioning, Parental Insightfulness, and Mind-Mindedness, alongside father-child attachment processes and fathers' emotional regulation, in enhancing children's socio-emotional competencies and social adaptation [16,28,[113][114][115]. Thus, future research could integrate these factors comprehensively to thoroughly explore the unique role of fathers in children's development.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in the context of societal transformations, with mothers increasingly entering the workforce and fathers returning home to take on more childcare responsibilities, there has been a gradual equalization of parental roles between fathers and mothers within the family [27]. Consequently, the paternal influence on child rearing has gained increasing recognition [16,20,28]. Additionally, empirical research has also demonstrated that fathers and mothers played distinct roles and exhibited unique characteristics in their parenting approaches [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The recent systematic review by Larsson et al (2022) points out the importance of considering the triad after a child's premature birth. The systematic review conducted by Charpentier Mora et al (2023) confirmed the influence of paternal mentalizing on both the fathers' parenting features and the child's outcomes. It is therefore crucial to investigate the role played by paternal representations, particularly fathers' mentalizing specific influence, in the context of preterm birth.…”
Section: Theoretical Implications and Perspectives For Future Researchmentioning
confidence: 93%
“…We suggest the potential posttraumatic growth of veteran parents who experienced pre-military physical trauma. While contemporary research on parental mentalization has been largely mother-centric (Charpentier Mora et al, 2023), our study, with its focus on veteran parents, underscores the vital role of paternal mentalization in the realm of parenting.…”
Section: Strengthsmentioning
confidence: 93%